Research methods and statistics in psychology - Haslam, S. Alexander; McGarty, Craig
This book provides students with a highly readable and comprehensive introduction to the challenges of conducting research in psychology. The book guides readers through the range of choices involved in design, analysis, and presentation, and is supplemented by a range of practical learning features. These draw on the authors' extensive experience as frontline researchers, and provide step-by-step guides to quantitative and qualitative methods and analysis. Written in an accessible and engaging style, this text encourages deep engagement with its subject matter and is designed to communicate and cultivate passion for the research process as a whole. A comprehensive guide to the process of conducting psychological research from the ground up -- covering multiple methodologies, experimental and survey design, data analysis, ethics, and report writing. Detailed step-by-step guides to running analyses using SPSS as well as extended coverage of qualitative methods. Numerous thought-provoking examples of issues raised by contemporary research. An extensive range of learning aids and on-line resources. Written in an accessible style aimed at those starting out in psychology, but also relevant for advanced students and experienced researchers, this text will be essential reading for psychology students taking a research methods course for the first time.
Keywords: Psychology; Psychology, Experimental; Psychometrics; Psychology, Experimental; Psychology; Psychometrics; Ethik; Forschung; Methodologie; Psychologie; Statistik